Experimental validation of the Burgio–Rojac model of planetary ball milling by the length control of multiwall carbon nanotubes. (August 2016) - Kozma, G.; Puskás, R.; Papp, I.Z.; Bélteky, P.; Kónya, Z.; Kukovecz, Á.
Abstract: Multiwall carbon nanotubes (MWCNTs) were used as a model system to verify the applicability of the Burgio–Rojac milling map for describing top-down attrition phenomena in the submicrometer range. The nanotubes were milled using several different operation parameter sets in a planetary ball mill. Transmission electron micrographs of the products were analyzed to assess length reduction and Raman spectra were recorded to evaluate the extent of milling-induced amorphization from the intensity ratio of the D and G lines. A simple statistical model describing MWCNT length reduction was established and different data representations were compared against the predictions of this model. While it was not possible to fully interpret the resulting data as functions of the typically considered primary milling parameters, the derivative parameter space defined by the individual ball impact energy and cumulative transferred energy variables calculated from the Burgio–Rojac model provided a satisfactory reference frame. The single hit threshold energy for successful MWCNT attrition was determined to be approx. 35 mJ/hit.